1989
DOI: 10.1002/jso.2930410316
|View full text |Cite
|
Sign up to set email alerts
|

Proximal colostomy: Still an effective emergency measure in obstructing carcinoma of the large bowel

Abstract: Large bowel obstruction constitutes an emergency abdominal condition and necessitates prompt surgical treatment. The optimal approach is still controversial as to whether to perform a diverting colostomy only or a tumor resection with or without primary anastomosis. Seventy-one elderly and high-risk patients were treated by proximal diverting colostomy through a right upper abdominal incision. The operative mortality was 8.5%, with an additional morbidity of 20.5%. Stomal complications appeared in 6.1% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This shows the need for further improvements in surgical techniques. The complication rate of this study (29%) is well in line with previous research [4,[19][20][21][22][23][24][25][26]. In a large registry study, Cottam, et al identified 34% of 3970 stomas as problematic [4].…”
Section: Discussionsupporting
confidence: 90%
“…This shows the need for further improvements in surgical techniques. The complication rate of this study (29%) is well in line with previous research [4,[19][20][21][22][23][24][25][26]. In a large registry study, Cottam, et al identified 34% of 3970 stomas as problematic [4].…”
Section: Discussionsupporting
confidence: 90%
“…Traditional three-staged resection is out of favor nowadays because only 70 to 80 percent could undergo subsequent resection. 19 Resection of the tumor without anastomosis, i.e., two-staged resection or Hartmann's operation, is a safe option for most surgeons. Recently, promising results on one-staged resection and anastomosis with segmental resection after antegrade on-table irrigation or subtotal colectomy have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…When the cumulative morbidity and mortality are taken into account, an initial loop colostomy does not offer any survival advantage and has the disadvantages of a prolonged hospital stay and exposure of patients to repeated operations 11 . This procedure has been largely reserved for the patient who is unstable during surgery or when the surgical team is inexperienced 12 .…”
Section: Introductionmentioning
confidence: 99%